Oral Gastrografin Facilitates Delineation of Intestinal Tracts in CT-Based Brachytherapy for Uterine Cervical Cancer - Irie, Daisuke (Cureus, 2020)
Three-dimensional image-guided brachytherapy (3D-IGBT) using computed tomography (CT) is an essential component of definitive radiation therapy for uterine cervical cancer (UCC). Treatment planning for CT-based 3D-IGBT requires delineating the high-risk clinical target volume (CTV(HR)) and the organs at risk (OARs), which is difficult when the small intestine is adjacent to those delineation targets. Uncertainty in target delineation threatens the validity of 3D-IGBT treatment plans. To address this issue, we introduce the use of diatrizoate meglumine and diatrizoate sodium (gastrografin), an orally administrable iodine-based radiopaque contrast agent. We present two cases of UCC treated with CT-based 3D-IGBT and describe how intraluminal enhancement of the small intestine by oral gastrografin pretreatment facilitated discrimination between the small intestine and the adjacent CTV(HR) (case no.1) or the rectosigmoid colon (case no. 2). Oral gastrografin pretreatment is a simple and cost-effective method that allows distinguishing the small intestine from the adjacent delineation target (i.e., CTV(HR) and the OARs) in CT-based 3D-IGBT for UCC.